The effect of responses to vernalization, photoperiodism, and earliness per se of barley accessions from Dagestan on the duration of the period from shooting to heading - I. A. Zveinek; R. A. Abdullaev; B. A. Batasheva; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. Paratypic variability of the development rates of barley accessions from the Republic of Dagestan was analyzed for five years in the Northwe st of Russia (Pushkin, St. Petersburg) and in the North Caucasus (Derbent, Dagestan). Responses to vernalization, photoperiodism and earliness per se were tested in contrasting environments to assess their effect on barley development. Such studies make it possible to identify valuable adaptable plant forms in the barley germplasm collection for further use in breeding practice.Materials and methods. In Dagestan, the duration of the period from shooting to heading was measured for 12 samples of barley accessions in winter and spring sowing trials. Twenty samples sown in spring in both regions were compared. An empirical indicator of plant development rate was used for barley: the criterion “the number of days by which the period from shooting to heading of an accession exceeds the minimum across a sample” (DPSH).Results and conclusions. Early barley accessions with a low norm of responsiveness were identified: k-3772, k-15013, k-15034, k-15036, k-15186, k-15192, k-21803 and k-23785 – they combined weak sensitivity to a short photoperiod and vernalizing temperatures, so they are promising for breeding in regions where the length of the growing season is a limiting factor. The effect of the responses of barley accessions from Dagestan to vernalization and a short photoperiod on the duration of the period from shooting to heading was on average 8 (5.1–10.6) days and on their earliness per se 6 (4.8–8.2) days. Paratypic variability reflects the range of variation for these indicators. In Dagestan, vernalization temperatures and insensitivity to a short day are the main factors determining the earliness of local barleys in their native environment.